PENGARUH PRESIPITASI, WAKTU DAN RESPON HALUSINASI TERHADAP DURASI HALUSINASI PASIEN SKIZOFRENIA DI RSJ PROF. DR. SOEROJO MAGELANG - Abdul Jalil (Jurnal Kesehatan, 2021)
Background : Schizophrenia patients often experience hallucinations, confused speech, delusions(1). Hallucinations led to the decline in performing daily activities, loss of motivation and responsibility, refrain from social relations(2). Disturbing hallucinations is a risk of violent behavior(3). Currently there is no study on the effects of precipitation, time and duration of response to hallucinations. Nurses need to know about it to help select the appropriate alternative interventions so that the duration of the hallucinations can be shortened. Objective : to determine the effect of the characteristics of hallucinations (precipitation, time and response) for the duration of the hallucinations of schizophrenia patients in Prof. Dr. Soeroyo Mental Hospital Magelang. Method : This research is a correlational research using cohort design. The research subjects are schizophrenia patients that cared in quiet room in the hospital. Precipitation factors, time, response and the duration of hallucinations are the studied variables. The number of sample is 127 respondents using accidental sampling technique. Data were collected using questionnaire from October 2009 to September 2011. The data were analyzed using univariate and bivariate Chi Square. Result : 30.7% of the respondents experience hallucinations at night. The respondents that response in anger when the hallucinations come up are 40.2%, while 35.4% of the respondents were happy. There are 33.9% respondents who have biopsychosociocultural precipitation. The respondents who have the duration of hallucinations ≤ 12 days are as much as 59.8%, whereas 40.2% of the respondents experience the durations of hallucinations of more than 12 days. There is an influence of precipitation with a duration of hallucinations (sig 0.027), and also there is an influence of time with a duration of hallucinations (sig 0.002). The relationship between the response with a duration of hallucinations is also exist (sig 0.001). Conclusion : precipitation, response and the time of hallucinations influence the duration of the hallucinations. Biopsycologic factors and anger response have a shorter duration of hallucinations, as well as hallucinations that occur in the morning and afternoon.